MACC1 promotes pancreatic cancer metastasis by interacting with the EMT regulator SNAI1 - Xianglian Zhang; Ya Luo; Yu Cen; Xin Qiu; Jing Li; Mengmeng Jie; Shiming Yang; Shanyu Qin (Cell Death and Disease, 2022)
Abstract Metastasis is the dominant cause of cancer-related mortality. Metastasis-associated with colon cancer protein 1 (MACC1) has been proven to play a critical role in cancer metastasis. However, the prometastatic role of MACC1 in regulating the pancreatic cancer (PC) metastatic phenotype remains elusive. Here, we report that MACC1 is highly expressed in The Cancer Genome Atlas (TCGA) and tissue microarray (TMA) and identified as a good indicator for poor prognosis. Overexpression or knockdown of MACC1 in PC cells correspondingly promoted or inhibited pancreatic cancer cell migration and invasion in a MET proto-oncogene receptor tyrosine kinase (MET)-independent manner. Notably, knockdown of MACC1 in PC cells markedly decreased the liver metastatic lesions in a liver metastasis model. Mechanistically, MACC1 binds to the epithelial-mesenchymal transition (EMT) regulator snail family transcriptional repressor 1 (SNAI1) to drive EMT via upregulating the transcriptional activity of SNAI1, leading to the transactivation of fibronectin 1 (FN1) and the trans-repression of cadherin 1 (CDH1). Collectively, our results unveil a new mechanism by which MACC1 drives pancreatic cancer cell metastasis and suggest that the MACC1-SNAI1 complex-mediated mesenchymal transition may be a therapeutic target in pancreatic cancer.